Why Do Indonesian Users Remain Loyal to Digital Subscriptions? Examining Endowment Effect, Commitment Bias, Hedonic Motivation, and Switching Costs - Kembau, Agung Stefanus; Mandey, Nancy Henrietta Jessamine; Tampinongkol, Felliks Feiters; Makarawung, Reynard Justino Nehemia (Universitas Diponegoro, 2025)
Subscription‐based platforms have become pivotal to digital business models, yet little is known about the psychological forces that bind customers to these services in emerging markets. Drawing on behavioral economics, this study theorizes that endowment effect and commitment bias build consumer loyalty by strengthening users’ perceived ownership and rationalizing prior choices. We further propose that hedonic motivation (enjoyment derived from service use) and switching costs (economic and psychological barriers to change) intensify these effects. Data from 224 digital-service subscribers in Greater Jakarta were analyzed with covariance-based structural equation modeling in SmartPLS. All six hypotheses are supported: both endowment effect (β = .32, p < .001) and commitment bias (β = .29, p < .001) directly enhance loyalty, while their impacts are amplified by hedonic motivation (interaction β = .14, p < .01) and switching costs (interaction β = .18, p < .01). The findings extend loyalty theory by positioning endowment and commitment as dual psychological anchors in subscription contexts and by identifying boundary conditions that magnify their influence. For managers, the results stress the value of fostering user ownership feelings, designing engaging service experiences, and deliberately increasing perceived costs of defection to boost retention. Collectively, the study offers a nuanced framework for understanding—and managing—the drivers of sustained patronage in rapidly growing digital economies.